2020
DOI: 10.3390/medicina56030126
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility-related Adverse Events Following HeartMate II Left Ventricular Assist Device Implantation between Japan and United States

Abstract: Background: Left ventricular assist device (LVAD) therapy has improved the clinical outcomes in advanced heart failure patients, however, this may differ between countries. We aimed to compare outcomes between Japanese and US LVAD cohorts. Methods: For 416 consecutive LVAD patients who received HeartMate II LVAD implantation and completed a one-year follow-up, age-matched Japanese patients (the Japanese registry for mechanically assisted circulatory support (J-MACS) group) and the US patients were compared for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A review of J-MACS data demonstrated a higher stroke rate in a Japanese cohort as compared with an agematched USA LVAD cohort treated at a single center (0.221 vs. 0.052/patient-year, p = 0.005), though the cohort in the single center may not necessarily represent the overall USA cohort. 34 This difference between the countries could be explained by differences in multiplefactors including genetics, salt sensitivity, body size, and heart failure etiology. Samura and colleagues investigated risk factors for stroke after CF-LVAD implantation in 158 Japanese patients and found that LVAD patients with an early stroke (within 90 days) had a significantly lower pump output within 24 h after LVAD implantation (3.4 vs. 4.0 L/min) and significantly higher LDH level within 2 weeks.…”
Section: Hemocompatibility-related Complications Including Stroke And...mentioning
confidence: 99%
See 1 more Smart Citation
“…A review of J-MACS data demonstrated a higher stroke rate in a Japanese cohort as compared with an agematched USA LVAD cohort treated at a single center (0.221 vs. 0.052/patient-year, p = 0.005), though the cohort in the single center may not necessarily represent the overall USA cohort. 34 This difference between the countries could be explained by differences in multiplefactors including genetics, salt sensitivity, body size, and heart failure etiology. Samura and colleagues investigated risk factors for stroke after CF-LVAD implantation in 158 Japanese patients and found that LVAD patients with an early stroke (within 90 days) had a significantly lower pump output within 24 h after LVAD implantation (3.4 vs. 4.0 L/min) and significantly higher LDH level within 2 weeks.…”
Section: Hemocompatibility-related Complications Including Stroke And...mentioning
confidence: 99%
“…A review of J‐MACS data demonstrated a higher stroke rate in a Japanese cohort as compared with an age‐matched USA LVAD cohort treated at a single center (0.221 vs. 0.052/patient‐year, p = 0.005), though the cohort in the single center may not necessarily represent the overall USA cohort 34 . This difference between the countries could be explained by differences in multiple‐factors including genetics, salt sensitivity, body size, and heart failure etiology.…”
Section: Durable Mechanical Circulatory Support For End‐stage Heart F...mentioning
confidence: 99%
“…Recently, therapies including omega-3 fatty acid and digoxin administration were found to be associated with fewer gastrointestinal bleeding events, possibly due to suppression of these maladaptive cascades [30][31][32]. Genetic and dietary factors might also have a considerable impact on angiogenesis activity, given a considerably lower observed incidence of gastrointestinal bleeding in Japanese cohorts [33]. Further molecular biological analyses are warranted to clarify the relationship between hemodynamics, the angiogenesis cascade, and gastrointestinal bleeding.…”
Section: Gastrointestinal Bleedingmentioning
confidence: 99%
“…Bleeding complications in organs, including the gastrointestinal system and the brain, are major concerns in our center. We also suspect that there may be genetic or racial differences between the Asian and Western population (3)(4)(5). We hope that HeartMate3 may reduce the incidence of bleeding complications.…”
mentioning
confidence: 99%